Electrical characterization of p-GeSn/n-Ge diodes with interface traps under dc and ac regimes. (August 2015) - Baert, B.; Gupta, S.; Gencarelli, F.; Loo, R.; Simoen, E.; Nguyen, N.D.
Abstract: In this work, the electrical properties of p-GeSn/n-Ge diodes are investigated in order to assess the impact of defects at the interface between Ge and GeSn using temperature-dependent current–voltage and capacitance–voltage measurements. These structures are made from GeSn epitaxial layers grown by CVD on Ge with in situ doping by Boron. As results, an average ideality factor of 1.2 has been determined and an activation energy comprised between 0.28 eV and 0.30 eV has been extracted from the temperature dependence of the reverse-bias current. Based on the comparison with numerical results obtained from device simulations, we explain this activation energy by the presence of traps located near the GeSn/Ge interface.